Հայոց ցեղասպանության համար նյութական պատասխանատվության խնդիրը և Մեծ Բրիտանիան (1915-1924 թթ.) - Տիգրան Սարուխանյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается вопрос о финансовых аспектах ответственности за Геноцид армян в контексте политики Англии 1915— 1924 гг. Во время Первой мировой войны депозитированные в немецком Рейхсбанке деньги армян были переведены в Лондон и присвоены британским правительством. The article examines the large aspects of financial responsibility for the Armenian Genocide, in the context of policy of England in 1915-1924 which forced the crime to become not only politically, but also financially denied and rejected. Moreover, the British Government, its politicians,financiers and diplomats were largely engaged in the process of pocketing 5 000 000 Turkish pounds in gold, which was robbed by the Turkish Government from the Armenians during World War I, deposited in German Reichsbank and, then transferred to London and, appropriated by the former.
Keywords: History; Political Science; Armenian Genocide (1915); Great Britain; D History; J Political Science